GC–MS and GC–IR Analyses of the Methoxy-1-n-pentyl-3-(1-naphthoyl)-indoles: Regioisomeric Designer Cannabinoids. (16th June 2018) - Thaxton-Weissenfluh, Amber; Belal, Tarek S; DeRuiter, Jack; Smith, Forrest; Abiedalla, Younis; Neel, Logan; Abdel-Hay, Karim M; Clark, C Randall
Abstract: The indole ring regioisomeric methoxy-1- n -pentyl-3-(1-naphthoyl)-indoles represent indole ring-substituted analogs of the synthetic cannabinoid JWH-018. The electron ionization mass spectra show equivalent regioisomeric major fragments resulting from cleavage of the groups attached to the central indole nucleus. The characteristic (M-17) + fragment ion at m/z 354 resulting from the loss of OH group is significant in the mass spectra of all four compounds. Fragmentation of the naphthoyl and/or pentyl groups yields the cations at m/z 314, 300, 244 and 216. The vapor-phase infrared spectra provide a number of characteristic absorption bands to identify the individual isomers. Gas chromatographic separations on a capillary column containing a film of trifluoropropylmethyl polysiloxane (Rtx-200) provided excellent resolution of these compounds, their precursor indoles and intermediate pentylindoles. The elution order appears related to the degree of crowding of indole ring substituents.